Association between obesity and mortality in the Costa Rican elderly: a cohort study - Carolina Santamaría-Ulloa; Anne Chinnock; Melina Montero-López (BMC, 2022)
Abstract Background Costa Rica, along with other Latin American countries, is undergoing population aging, with an increase in the prevalence of chronic conditions, many of them resulting from a growing prevalence of obesity. As a result of the demographic and epidemiological transitions, the causes of morbidity and mortality have changed from communicable to non-communicable diseases. An increase in overweight and obesity is hypothesized to be related to premature mortality. This study assesses the association between obesity and both all-cause and cardiovascular mortality in a Costa Rican elderly population. Methods This is a secondary data analysis of the Costa Rican Longevity and Healthy Aging Study (CRELES, for its Spanish acronym), a longitudinal nationally representative cohort study of health and life-course experiences of the Costa Rican elderly. A baseline (n = 2827) and two subsequent 2-year follow-up interviews were conducted. Data analyses include descriptive statistics and survival models. Cox and Gompertz distributions were used to model general mortality and cardiovascular mortality as a function of obesity and controlling for confounders. Anthropometric measures used were Body Mass Index (BMI) and Waist Circumference (WC). Results Each one-unit increment in BMI was significantly associated to a 3,1% (p < 0.001) and 2,6% (p = 0.021) increment in general and cardiovascular mortality respectively. Each one-unit increment in WC was significantly associated with a 0,8% (p = 0.006) increment in general mortality, whereas WC was not significantly associated with cardiovascular mortality. Conclusions Obesity is associated with mortality in the Costa Rican elderly. This association is strongest between obesity and all-cause mortality. As general obesity increases, all-cause and cardiovascular mortality also increase in this population. Similarly, as central obesity increases, all-cause mortality increases. Policies aimed at preventing obesity and chronic conditions are warranted for a better survival in this population.